Validation of PWR Neutronics Code Package TORCH V2.0 With Nuclear Power Plant Measurements - Zhang, Bin; Peng, Xingjie; Zhao, Chen; Zhao, Wenbo; Li, Qing (Frontiers in Energy Research, 2022)
This paper presents the validation and verification (V&V) of PWR neutronics code package TORCH V2.0 with nuclear power plant (NPP)measurements. The advanced nuclear power engineering design software TORCH V2.0 is developed by Nuclear Power Institute of China (NPIC), Chian National Nuclear Corporation (CNNC). Based on the two-step calculation scheme, TORCH V2.0 mainly contains lattice physics code for assemblyhomogenization, link calculation code for few-group constant parameterization and core simulationcode for few-group core calculation.The calculation modules of each code were already verified against various benchmarkproblems, whereas this paper focuses on the V&V of linked code system. The measured values of reactor startup physics test and nuclear power plant operation from five PWR NPPs (Daya BayNPP, Ling Ao NPP, Fangjiashan NPP, Qinshan NPP, Hainan Changjiang NPP, Fuqing NPP) are utilized to do the comparison and analysis for V&V.Compared parameters of reactor startup physics test contains critical boron concentration, control rod integral value, boron differential valueand isothermal temperature coefficient. Compared parameters of nuclear power plant operation contains critical boron concentration, assembly-wise power distribution, hot spot factor and nuclear enthalpy rise factor. The results show that the software TORCH V2.0 has reliable calculaition ability and is applicable to the PWR nuclear power engineering design which is based on square fuel assembly.